Helix-Loop-Helix Factor Id3 (Inhibitor of Differentiation 3): A Novel Regulator of Hyaluronan-Mediated Adipose Tissue Inflammation. Issue 2 (February 2021) - Misiou, Angelina; Garmey, James C.; Hensien, Jack M.; Harmon, Daniel B.; Osinski, Victoria; McSkimming, Chantel; Marshall, Melissa A.; Fischer, Jens W.; Grandoch, Maria; McNamara, Coleen A.
Abstract : Objective: The aim of this study was to unravel mechanisms whereby deficiency of the transcription factor Id3 (inhibitor of differentiation 3) leads to metabolic dysfunction in visceral obesity. We investigated the impact of loss of Id3 on hyaluronic acid (HA) production by the 3 HAS isoenzymes (HA synthases; -1, -2, and -3) and on obesity-induced adipose tissue (AT) accumulation of proinflammatory B cells. Approach and Results: Male Id3 −/− mice and respective wild-type littermate controls were fed a 60% high-fat diet for 4 weeks. An increase in inflammatory B2 cells was detected in Id3 −/− epididymal AT. HA accumulated in epididymal AT of high-fat diet–fed Id3 −/− mice and circulating levels of HA were elevated. Has2 mRNA expression was increased in epididymal AT of Id3 −/− mice. Luciferase promoter assays showed that Id3 suppressed Has2 promoter activity, while loss of Id3 stimulated Has2 promoter activity. Functionally, HA strongly promoted B2 cell adhesion in the AT and on cultured vascular smooth muscle cells of Id3 −/− mice, an effect sensitive to hyaluronidase. Conclusions: Our data demonstrate that loss of Id3 increases Has2 expression in the epididymal AT, thereby promoting HA accumulation. In turn, elevated HA content promotes HA-dependent binding of B2 cells and an increase in the B2 cells in the AT, which contributes to AT inflammation. Abstract : Supplemental Digital Content is available in the text.